Evaluation of Students’ Skills in Compounding of Divided Powders - M Rifqi Rokhman; Hardika Aditama; Angi Nadya Bestari (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Several types of medicines for pediatric patients are not commercially available in appropriate dosage forms. While divided powder resulted from compounding process is an alternative to address this problem, the dosage accuracy is still profoundly a major issue. This research was aimed at comparing student’s ability prior to and after taking compounding practical work and analyzing weight accuracy of divided powders compounded by students. This research was designed as a pre-post study. Students who were taking compounding practical work (for 12 weeks) in 2017 were asked to fill a prescription contained divided powders in the beginning and the end of the semester, given enriched learning material of compounding technique videos and feedback as evaluation of their pretest results. The data is presented in the form of a percentage, while differences between pretest and post-test are compared utilizing Wilcoxon test. This study suggests that there was a significant increase of students’ ability in calculating the amount of each ingredient required to fill the prescription, choice of label color, approximating the beyond-use date, folding the divided powders, and making a copy of the prescription. However, there was a small number of students (15.3%) whose divided powders they have dispensed were in the allowed weight range. This study documents the need for quality assessment of medications prepared by students quantitatively and this assessment serves as a parameter of student performance.